Analisis Semiotik PidatoPelantikan GubernurDKI Jakarta Anies Baswedan - Simanjuntak, Sahata (Institut Agama Islam Negeri (IAIN) Curup, 2018)
First speech as governor DKI Jakarta was did by Anies Baswedan political communication step to consolidate Jakarta society after DKI Jakarta election. Phrasing content and choosing diction was important things in the formal speech. Phrasing pribumi word was forbidden by law to use, this make blunder for Anies team after contestation with incumbent rival the governor before who was lose, and this make pro and contra in DKI Jakarta society. This research was talked about semiotic analysis using triangle meaning theory Charles Sander Pierce for critic and interpretation descriptify speech governor DKI Jakarta Anies Baswedan content with â€œpribumiâ€ word was made pro and contra in society life. Anies figure was knowed as an academic who achieved in country and international also served in some strategys position, considered not conscientious phrasing legal speech content ideal was mastered goodly by Anis Baswedan who did good legal speech even without teks. So make some question for researcher how actually content and situation was did speech by Anies. The interpretation of the use of the native word as a sign gives a negative image because it legally violates the president's instructions. But the use of the native word interpreted as an emergency word delivered by Anis represents a sense of injustice experienced by most of the Jakarta community in the context of his speech. This is an indicator that the majority of the people feel the injustice of their rivals whose note is the previous incumbent.